(х-4)(4х+6)=(х-5)^2 P.S. ^-это степень

0 голосов
18 просмотров

(х-4)(4х+6)=(х-5)^2

P.S. ^-это степень


Алгебра (24 баллов) | 18 просмотров
Дано ответов: 2
0 голосов

4x^2+6x-16X-24=x^2-10x+25

4x^2-x^2+6x-16x+10x-24-25=0

3x^2-49=0

3x^2=49 перенесли в противоположную сторону меняя знак

3x^2=49

x^2=49/3

x^2=16,3

x1=корень из 16,3

х2=минус корень из 16,3

 

(372 баллов)
0 голосов

4x^2+6x-16X-24=x^2-10x+25

4x^2-x^2+6x-16x+10x-24-25=0

3x^2=49 

x^2=49/3

x^2=16,3

x1=корень из 16,3

х2=минус корень из 16,3

(104 баллов)